Activating a hematite nanorod photoanode via fluorine-doping and surface fluorination for enhanced oxygen evolution reaction - Wang, Chenglong; Wei, Shenqi; Li, Feng; Long, Xuefeng; Wang, Tong; Wang, Peng; Li, Shuwen; Ma, Jiantai; Jin, Jun (Nanoscale, 2020)
Poor charge separation and sluggish oxygen evolution reaction (OER) kinetics are two typical factors that hinder the photoelectrochemical (PEC) applications of hematite. Dual modification via heteroatom doping and surface treatment is an attractive strategy to overcome the above problems. Herein, for the first time, a hematite nanorod photoanode was ameliorated via the fluorine treatment (F-treatment) of both bulk and surface, enabling simultaneous charge separation from the interior to the interface. Accordingly, the novel photoanode (FeF x /F-Fe 2 O 3 ) exhibited an outstanding PEC water oxidation activity, with a 3-fold improved photocurrent density than that obtained using unmodified α-Fe 2 O 3 . More specifically, fluorine doping (F-doping) in the hematite bulk remarkably increased the concentration of charge carriers and endowed it with favorable electrical conductivity for rapid charge transfer. Further surface F-treatment on F-doped α-Fe 2 O 3 (F-Fe 2 O 3 ) enriched the F–Fe bonds on the surface, which significantly boosted the OER kinetics and thereby inhibited the detrimental charge recombination. As a consequence, the efficiencies of bulk electron–hole pair separation and surface hole injection increased by 2.8 and 1.7 times, respectively. This study points to fluorine modulation as an attractive avenue to advance the PEC performance of metal oxide-based photoelectrode materials.